Bible Study in Geneva: Theological Training for the Preachers to the People - De Boer, EA (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
This article argues the historical situation, the purpose, the contents and the functions of the ecclesiastical institution called la congrégation in Calvin’s Geneva. In doing this primary sources are consulted and a comprehensive view of this significant body is offered. In the critical assessment of these sources it became clear that both the interpretation (study) of Scripture and the formulation of doctrine were the focus of the congrégation. Exposition and discussion were essentially connected. As a matter of fact, these Bible studies were intended for ongoing training of the ministers. The purpose of the meetings was indeed to preserve purity and concord in doctrine. This was achieved by the exegeses of Biblical books, homiletically training, related disputations of propositions with a strong accent on doctrine and brotherly censure according to the standards of orthodoxy. The article shows that the congrégations also effectuated Calvin’s choice of Biblical books to be explained in commentaries, it served as an instrument of instructing lay people (who regularly attended the meetings), the examination of candidates for the ministry and the formulation of doctrine.